Anatomy of the Inferior Orbital Fissure: Implications for Endoscopic Cranial Base Surgery - De Battista, Juan Carlos; Zimmer, Lee A.; Theodosopoulos, Philip V.; Froelich, Sebastien C.; Keller, Jeffrey T. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Considering many approaches to the skull base confront the inferior orbital fissure (IOF) or sphenomaxillary fissure, the authors examine this anatomy as an important endoscopic surgical landmark. In morphometric analyses of 50 adult human dry skulls from both sexes, we divided the length of the IOF into three segments (anterolateral, middle, posteromedial). Hemotoxylin- and eosin-stained sections were analyzed. Dissections were performed using transnasal endoscopy in four formalin-fixed cadaveric cranial specimens (eight sides); three endoscopic approaches to the IOF were performed. IOF length ranged from 25 to 35 mm (mean 29 mm). Length/width of the individual anterolateral, middle, and posteromedial segments averaged 6.46/5, 4.95/3.2, and 17.6/ 2.4 mm, respectively. Smooth muscle within the IOF had a consistent relationship with several important anatomical landmarks. The maxillary antrostomy, total ethmoidectomy approach allowed access to the posteromedial segment of the fissure. The endoscopic modified, medial maxillectomy approach allowed access to the middle and posterior-medial segment. The Caldwell-Luc approach allowed complete exposure of the IOF. The IOF serves as an important anatomic landmark during endonasal endoscopic approaches to the skull base and orbit. Each of the three segments provides a characteristic endoscopic corridor, unique to the orbit and different fossas surrounding the fissure.
Keywords: skull base; endoscope; inferior orbital fissure; orbit; pterygopalatine fossa